Home-Based Women Workers Vulnerability during the COVID-19: A Gendered Perspective of Political Economy - Ashilly Achidsti; Cinintya Audori Fathin (Magister Administrasi Publik, 2022)
This research uses a gender perspective to explore the condition of home-based women workers during the COVID-19 pandemic and analyze coping mechanisms adopted to mitigate the social and economic vulnerability. By applying the feminist political economy framework, the research focused on the vulnerability of home-based women workers in the Special Region of Yogyakarta (DIY), Indonesia. Home-based women's enterprises constitute a major component of the local businesses. This research used a qualitative research design. Results showed that home-based women workers (PPR) are exposed to six traits of vulnerability, namely: Workers' exploitation and low wage standard; lack of social security; nonexistence of job guarantee and weak law protection; bearing the work risk that should be the employers' obligation; low bargaining position; and unregulated working hours. In addition, compounded by inadequate education and high domestic responsibilities, these women are vulnerable to political and economic conditions that are in part attributable to the societal context they find themselves in. However, amid these vulnerabilities, home-based women workers in DIY have developed resilience through community networks supported by a local NGO called YASANTI. Thus, local NGOs have played a significant role in strengthening PPR resilience in DIY.